2014
DOI: 10.1097/jsc.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High Intensity Short Rest Resistance Exercise on Muscle Damage Markers in Men and Women

Abstract: Within and between sexes, universal load prescription (as assigned in extreme conditioning programs) creates extreme ranges in individual training intensities. Exercise intensity has been proposed to be the main factor determining the degree of muscle damage. Thus, the purpose of this study was to examine markers of muscle damage in resistance-trained men (n = 9) and women (n = 9) from a high intensity (HI) short rest (SR) (HI/SR) resistance exercise protocol. The HI/SR consisted of a descending pyramid scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 38 publications
2
39
2
3
Order By: Relevance
“…In contrast, while there were significant main effects for time in the present study, there were no differences between groups for IL-10, IL1-ra, and MCP-1 response. The differences in training status and/or workload during the strength exercise sessions may explain the discrepancy in results between the present and previous studies as subjects in Heavens et al (2014), and Rossi et al (2016) were resistance trained while the subjects in the present study were not.…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast, while there were significant main effects for time in the present study, there were no differences between groups for IL-10, IL1-ra, and MCP-1 response. The differences in training status and/or workload during the strength exercise sessions may explain the discrepancy in results between the present and previous studies as subjects in Heavens et al (2014), and Rossi et al (2016) were resistance trained while the subjects in the present study were not.…”
Section: Discussioncontrasting
confidence: 85%
“…Since BFR exercise is commonly performed at very low intensities (i.e. 20%-30% of 1RM), it is very unlikely that the mechanisms known for evoking muscle damage during traditional resistance training such as physical damage to muscle fibers due to high mechanical stress associated with high intensities and volumes [1,4], is applicable to this model of exercise. Therefore, perhaps a more reasonable explanation for the muscle damage linked to BFR exercise would be more metabolic in nature with increases in hydrogen ions concentrations, stimulation of the endocrine system, or an increase in reactive oxygen species.…”
Section: Aop Pressuresmentioning
confidence: 99%
“…It has also been suggested that exercise intensity and exercise volume may play a role in the exercise-induced muscle damage response [1]. Thus, it is worth noting many of the previous BFR studies performed BFR exercise at high volumes (75 reps) [39] or until failure [40].…”
Section: Aop Pressuresmentioning
confidence: 99%
See 2 more Smart Citations